1997
DOI: 10.1523/jneurosci.17-09-03038.1997
|View full text |Cite
|
Sign up to set email alerts
|

ENC-1: A Novel MammalianKelch-Related Gene Specifically Expressed in the Nervous System Encodes an Actin-Binding Protein

Abstract: We have identified and characterized a novel murine gene, , that is an early and highly specific marker of neural induction in vertebrates. ENC-1, which encodes a kelch family related protein, is expressed during early gastrulation in the prospective neuroectodermal region of the epiblast and later in development throughout the nervous system (NS). ENC-1 expression is highly dynamic and, after neurulation, preferentially defines prospective cortical areas. The only apparent expression of ENC-1 outside the NS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 68 publications
2
81
1
2
Order By: Relevance
“…It should also be noted that when Krp1-myc was expressed in 208F cells, and when we examined the low level of endogenous Krp1 that is present in FBR-TAM67 cells, no co-localization with F-actin containing stress ®bres was detected. This result contradicts work presented by Hernandez et al, (1997) and Soltysik-Espanola et al (1999), who reported that two other kelch family members, ENC1 and Mayven, interact with stress ®bres containing F-actin. Together these data suggest that Krp1 only co-localizes with F-actin when it is in the looped membrane ru e-like structure at the tips of pseudopodia.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It should also be noted that when Krp1-myc was expressed in 208F cells, and when we examined the low level of endogenous Krp1 that is present in FBR-TAM67 cells, no co-localization with F-actin containing stress ®bres was detected. This result contradicts work presented by Hernandez et al, (1997) and Soltysik-Espanola et al (1999), who reported that two other kelch family members, ENC1 and Mayven, interact with stress ®bres containing F-actin. Together these data suggest that Krp1 only co-localizes with F-actin when it is in the looped membrane ru e-like structure at the tips of pseudopodia.…”
Section: Discussioncontrasting
confidence: 99%
“…Another protein, alpha-scruin of Limulus, which has kelch repeats present at both its amino and carboxyl termini but lacks a BTB/POZ domain, cross-links actin ®laments within the acrosomal processes of sperm (Way et al, 1995a). Further kelch proteins are also thought to interact with actin: murine and human ENC1 (Hernandez et al, 1997(Hernandez et al, , 1998; spe-26 of C. elegans (Varkey et al, 1995); and human Mayven (Soltysik-Espanola et al, 1999). Many other family members are thought not to interact with actin; beta-scruin of Limulus, for instance, is found in sperm acrosomal vesicles, which do not contain actin (Way et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations